2021
DOI: 10.3390/cells10061358
|View full text |Cite
|
Sign up to set email alerts
|

Longer Sperm Swim More Slowly in the Canary Islands Chiffchaff

Abstract: Sperm swimming performance affects male fertilization success, particularly in species with high sperm competition. Understanding how sperm morphology impacts swimming performance is therefore important. Sperm swimming speed is hypothesized to increase with total sperm length, relative flagellum length (with the flagellum generating forward thrust), and relative midpiece length (as the midpiece contains the mitochondria). We tested these hypotheses and tested for divergence in sperm traits in five island popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 89 publications
0
16
1
Order By: Relevance
“…In our analysis of we found two key outcomes. We did not find a positive relationship between total sperm length and VCL, again emphasizing the general the mix of studies where total sperm length and sperm velocity do [ 16 , 61 ] or do not relate to each other [ 19 , 20 , 21 ]. Sperm length in each of our clusters was driven almost entirely by flagellum length ( Supplementary Figure S1 ), which could suggest that this is a key component of sperm speed.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In our analysis of we found two key outcomes. We did not find a positive relationship between total sperm length and VCL, again emphasizing the general the mix of studies where total sperm length and sperm velocity do [ 16 , 61 ] or do not relate to each other [ 19 , 20 , 21 ]. Sperm length in each of our clusters was driven almost entirely by flagellum length ( Supplementary Figure S1 ), which could suggest that this is a key component of sperm speed.…”
Section: Discussionmentioning
confidence: 59%
“…In turn, it is often assumed that selection for faster swimming speeds has driven an increase in length of sperm and many studies across [ 14 , 16 ] and within species [ 17 , 18 ] have shown a positive length-speed relationship. Nonetheless, within species the relationship between sperm length and velocity is not consistent (e.g., [ 19 , 20 , 21 ]) with several key factors thought to alter the relationship. Individual male quality [ 22 ] or reproductive tactics [ 23 ] can lead to changes in sperm speed without changes in morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-individual variations in sperm size have been presented as a potential consequence of reduced sperm competition, therefore, relaxing selection on optimal sperm length [ 49 , 50 ]. Although it is typically believed that longer sperm swim faster, a study on the Canary Islands’ chiffchaff ( Phylloscopus canariensis ) found that longer sperm were slower, therefore not supporting the sperm morphology–swimming speed hypotheses presented by other groups where longer sperm were faster swimmers [ 51 ]. Thus, the relationship between sperm morphology and sperm motility should be investigated further with the Arabian bustard.…”
Section: Discussionmentioning
confidence: 99%
“…8: 211025 which is not required in birds [69]. (iii) With its helical shape, Passerine sperm is morphologically distinct from mammalian sperm, moves differently by spinning around its long axis with little bending of the tail [30] and thus probably follows different hydrodynamic models [70]. (iv) In birds, the females' sperm storage tubules provide an antioxidant environment that shields sperm from ROS-induced damage for prolonged periods of time (at least a week and up to several months), which is considerably longer than in mammals [33].…”
Section: Discussionmentioning
confidence: 99%